Analisis Pelayanan Tiket Terhadap Kepuasan Penumpang KM. Sinabung pada PT. Pelayaran Nasional Indonesia Cabang Surabaya - Yuliana; Poli, Sofyan (Universitas Hang Tuah, 2018)
PT. PELNI is a company engaged in the field of marine transportation services ie passenger ships. The importance of